2019
DOI: 10.1177/0734242x19886635
|View full text |Cite
|
Sign up to set email alerts
|

An empirical study on waste generation rates at different stages of construction projects in China

Abstract: Estimation of construction waste generation is critical to construction waste management decisions. However, current construction waste estimation methods have various limitations (e.g. small samples). To address those limitations, this research conducts an empirical study to evaluate the waste generation rate of different types of waste at different construction stages. In this study, construction waste from 148 new-built residential construction sites in China were sorted and weighted on site and their waste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Based on the project life cycle, starting from design, procurement, storage, and implementation are interconnected, the design factors had the greatest potential to minimize waste and had been highlighted in various empirical studies [19][20]. However, the factors directly related to construction waste contextually are only implementation factors related to design and storage factors.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the project life cycle, starting from design, procurement, storage, and implementation are interconnected, the design factors had the greatest potential to minimize waste and had been highlighted in various empirical studies [19][20]. However, the factors directly related to construction waste contextually are only implementation factors related to design and storage factors.…”
Section: Resultsmentioning
confidence: 99%
“…However, the damage to the environment has been caused by air pollution, climate change, shortage of natural resources, and increasing waste generation, particularly from the construction industry. These constructions contribute ~36% of total waste globally ( 28 ). South Asian countries have a poor history of road construction, while in addition, the construction at hillsides saw rock-falling, landslides, debris flow, snow avalanches, and road closers.…”
Section: The Impact Of the Chinese In-land Environmental Policiesmentioning
confidence: 99%
“…Wang et al based on an empirical study, evaluated the waste generation rate of different types of waste at different construction stages by sorting and weighting the construction waste from 148 new-built residential construction sites on-site in China, and they found that the amount of inorganic nonmetallic waste with a generation rate of 16.59 kg/m 2 was the highest among the five types of wastes (i.e., inorganic nonmetallic waste, organic waste, metallic waste, composite waste, and hazardous waste), while the waste generation rate for the underground construction stage, which was 27.57 kg/m 2 , was the highest among the three stages (i.e. underground stage, superstructure stage, and finishing stage) [ 13 ]. He et al calculated the output of CDW in China from 2000 to 2016 by using CDW generation calculation method, and they proposed that China's construction waste generation will increase by 3% each year [ 14 ].…”
Section: Introductionmentioning
confidence: 99%